The molecular determination of emm genotypes in non-group a beta-hemolytic streptococci isolated from clinical samples - Suna Kızılyıldırım; Cansu Önlen Güneri; Fatih Köksal (National Scientific Medical Center, 2021)
Objective: M protein is an important marker in epidemiological and phylogenetic surveillance of Beta-Hemolytic Streptococci. The aim of this study is to determine emm types and their distribution among the GCS/GGS strains isolated from clinical samples. Material and methods: The study includes 98 β-hemolytic streptococcus strains isolated from clinical samples in Çukurova University/Balcalı Hospital. 67 of these isolates, defined as serologic, of which 56 were identified as Streptococcus dysgalactiae subsp. equisimilis, 8 as S. anginosus and 3 as S.equi subsp.zooepedimicus, have been included in the study. These strains were also confirmed by the Vitek 2GP-ID system. These isolates were confirmed by the polymerase chain reaction (PCR) method with primers based on groESL sequences. PCR-sequence analysis method developed by the Centers for Disease Control (CDC) was used for typing according to emm polymorphism. Results: 56/67 (83.6%) isolates in which emm-PCR was determined as positive were typed by sequence analysis. The findings were identified using the CDC database, and the most common type was determined to be stG485 (51.85%), stG643 (12.96%) and stG6 (9.25%). Conclusion: Consequently, GCS/GGS should be treated more seriously in our country as in the whole world.